One-year effectiveness and safety of ustekinumab in ulcerative colitis: a multicenter real-world study from Italy. (2nd November 2021) - Chiappetta, Michele Francesco; Viola, Anna; Mastronardi, Mauro; Turchini, Laura; Carparelli, Sonia; Orlando, Adele; Biscaglia, Giuseppe; Miranda, Agnese; Guida, Laura; Costantino, Giuseppe; Scaldaferri, Franco; Bossa, Fabrizio; et al.
ABSTRACT: Background: Efficacy and safety of ustekinumab for the treatment of ulcerative colitis (UC) has been demonstrated in clinical trials, but few real-world data are available so far. The aim of this study was to assess effectiveness and safety of ustekinumab in a cohort of refractory UC patients. Methods: Data of patients with moderate to severe UC treated with ustekinumab were retrospectively collected. Primary endpoint was steroid-free clinical remission at weeks 24 and 52 of therapy. Secondary endpoints were treatment response, endoscopic remission, treatment persistence at 12 months and safety. Results: A total of 68 patients [males 63%; median (range) age 42 (16–72) years] were included. Almost all patients (97%) were biologics experienced. At weeks 24 and 52, 31% and 50% of patients achieved steroid-free clinical remission, 84% and 82% had clinical response, respectively. At the end of follow-up, there was a significant reduction of pMS from baseline (p < 0.001) and of steroid use (p < 0.001). At week 52, 22% of the available endoscopies (18/38) showed mucosal healing. The probability to persist in therapy at week 52 was 87%. Only one adverse event occurred. Conclusions: Data from our real-life cohort of refractory UC patients suggest satisfactory effectiveness and a good safety of ustekinumab.